Long non-coding RNA PVT1 (PVT1) affects the expression of CCND1 and promotes doxorubicin resistance in osteosarcoma cells - Zi Li; Jia-Ming Tian; Yi Chu; Hong-Yi Zhu; Jun-Jie Wang; Jun Huang (Journal of Bone Oncology, 2023)
Background: Acquired drug-resistance is the major risk factor for poor prognosis and short-term survival in patients with osteosarcoma (OS). Accumulating evidence has revealed that long noncoding RNAs (lncRNAs), including plasmacytoma variant translocation 1 (PVT1), play potential regulatory roles in the malignant development of OS. Considering the subcellular distribution of PVT1 as both nuclear and cytoplasmic lncRNA, a thorough exploration of its extensive mechanisms becomes essential. Methods: The GEO database was utilized for the acquisition of gene expression data, which was subsequently analyzed to fulfill the research objectives. The subcellular localization of PVT1 in OS cells was determined using fluorescence in situ hybridization (FISH) and quantitative real-time polymerase chain reaction (qRT-PCR). Additionally, the sensitivity of OS cells to doxorubicin was comprehensively evaluated through measurements of cell viability, site-specific proliferation capacity, and the relative expression abundance of multidrug resistance-related proteins (MRPs). In order to investigate the differential response of OS cells with varying levels of PVT1 expression to doxorubicin, pulmonary metastasis mice models were established for in vivo studies. Molecular interactions were further examined using the dual-luciferase assay and RNA immunoprecipitation assay (RIP) to analyze the binding sites of miR-15a-5p and miR-15b-5p on PVT1 and G1/S-specific cyclinD1 (CCND1) mRNA. Furthermore, the chromatin immunoprecipitation (ChIP) and dual-luciferase assay were employed to assess the transcriptional activation of the proto-oncogene c-myc (MYC) on the CCND1 promoter and identify the corresponding binding sites. Results: In doxorubicin resistant OS cells, transcription levels of PVT1, MYC and CCND1 were significantly higher than those in original cells. In vivo experiments demonstrated that OS cells rich in PVT1 expression exhibited enhanced tumorigenicity and resistance to doxorubicin. In vitro experiments, it has been observed that overexpression of PVT1 in OS cells is accompanied by an upregulation of CCND1, thereby facilitating resistance to doxorubicin. Nonetheless, this PVT1-induced resistance can be effectively attenuated by the knockdown of CCND1. Mechanistically, PVT1 functions as a competitive endogenous RNA (ceRNA) that influences the expression of CCND1 by inhibiting the degradation function of miR-15a-5p and miR-15b-5p on CCND1 mRNA. Additionally, as a neighboring gene of MYC, PVT1 plays a role in maintaining MYC protein stability, which further enhances MYC-dependent CCND1 transcriptional activity. Conclusion: The resistance of OS cells to doxorubicin is facilitated by PVT1, which enhances the expression of CCND1 through a dual mechanism. This findings offer a novel perspective for comprehending the intricate regulatory mechanisms of long non-coding RNA in influencing the expression of coding genes.